Testing an International Measure of Public Service Motivation: Is There Really a Bright or Dark Side?. Issue 1 (31st March 2017) - Rayner, Julie; Reimers, Vaughan; Chao, Chih‐Wei (Fred)
Abstract: 'Public service motivation' (PSM) is usually reported as a bright force although recent debate alludes to a dark side. Variables representing each side are, respectively, job satisfaction and burnout. This study tests for both the bright and potential dark direct effects of PSM and responds to calls to further validate the international PSM instrument developed by Kim et al. (2013 ). Using a sample of 455 local council workers in Australia, analysis confirmed that while the measure was robust and generalizable in its structure, none of the dimensions of PSM were found to influence either job satisfaction or burnout. Plausible explanations include contextual factors, nomological concerns with the measurement instrument, and the notion that PSM has a non‐significant influence on either. The implications of these findings are discussed and future research proposed. Abstract : Using a sample of 455 council workers in Australia this study further validates an international measure of Public Service Motivation (PSM) and contributes to the debate concerning a bright and dark side to PSM (represented by job satisfaction and burnout). Contextual factors and nomological concerns with the instrument are discussed.